2012
DOI: 10.2174/187152712799960709
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Delivery of Transition-Metal Chelators to the Brain: Oxidative Stress will Never See it Coming!

Abstract: The pathological lesions typical of Alzheimer disease (AD) are sites of significant and abnormal metal accumulation. Metal chelation therapy, therefore, provides a very attractive therapeutic measure for the neuronal deterioration of AD, though its institution suffers fundamental deficiencies. Namely, chelating agents, which bind to and remove excess transition metals from the body, must penetrate the blood-brain barrier (BBB) to instill any real effect on the oxidative damages caused by the presence of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…One example, is the potential use of nanomaterials to transport metal chelating agents to pathological sites of significant and abnormal metal accumulation within Alzheimer disease patients (132). Transition metal accumulations in Alzheimer disease brains are thought to have an important role in local oxidative reactions and pathological lesions.…”
Section: Nanotherapeutics Against Oxidative Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…One example, is the potential use of nanomaterials to transport metal chelating agents to pathological sites of significant and abnormal metal accumulation within Alzheimer disease patients (132). Transition metal accumulations in Alzheimer disease brains are thought to have an important role in local oxidative reactions and pathological lesions.…”
Section: Nanotherapeutics Against Oxidative Injurymentioning
confidence: 99%
“…Transition metal accumulations in Alzheimer disease brains are thought to have an important role in local oxidative reactions and pathological lesions. Metal-chelating agents with the assistance of nanocarriers that can cross the blood-brain barrier (regardless of their size and hydrophilicity), selectively bind, remove and “redox-silence” transition metals provide promising potential for therapeutic intervention (132). Engineered nanomaterials may be also act as targeted enhancers of oxidative stress for tumor or cancer therapy.…”
Section: Nanotherapeutics Against Oxidative Injurymentioning
confidence: 99%
“…It was shown that the incubation of hepatocytes with Cu ions rapidly increases the production of free radicals [ 19 ]. Having in mind all the roles of copper ions in the human body, as well all the mentioned pathological conditions linked with its imbalance in the human organism, it is not surprising that the possible antimicrobial, antiviral, anti-inflammatory, and antitumor potential of copper ion metal chelators is being thoroughly studied [ 7 , 20 ].…”
Section: Copper’s Role In the Human Organismmentioning
confidence: 99%
“…Certain chelators for Cu are hydrophilic and require small hydrophobic molecules to cross the blood-brain barrier (BBB) (Kenche and Barnham, 2011). However, nanoparticle delivery systems could be promising and intriguing methods for metal chelation in AD treatment (Bonda et al, 2012). This novel technology has been used in multiple studies to treat different illnesses (Hernando et al, 2016;Xiao et al, 2022;Guadarrama-Escobar et al, 2023).…”
Section: Potential Therapeutic Avenues 41 Copper Chelatorsmentioning
confidence: 99%